2021
DOI: 10.1017/s0007114521000751
|View full text |Cite|
|
Sign up to set email alerts
|

Anthropometric cut-points for discriminating diabetes and the metabolic syndrome among Arabs and Asians: the Kuwait Diabetes Epidemiology Program

Abstract: This study aimed to determine anthropometric cut-points for screening diabetes and metabolic syndrome (MetS) in Arab and South Asian ethnic groups in Kuwait; and to compare the prevalence of MetS based on the ethnic-specific waist circumference (WC) cut-point and the International Diabetes Federation (IDF), and American Heart Association/National Heart, Lung, and Blood Institute (AHA/NHLBI) WC criteria. The national population-based survey dataset of diabetes and obesity in Kuwait adults aged 18-60 years were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Also, a study among Arab and South Asian Residents in Kuwait presented men with more incidence of metabolic abnormalities including hypertension, elevated FPG, and TG in both Arabs and South Asian groups. Abnormal low levels of HDL-C, was seen in Arab men more than Arab women, but it was higher among Asian women than men 46 . In the East of Asia, specifically China, more women had an abnormal WC, HDL-C, TC, and LDL-C compared to men, whereas hypertension, elevated TG and FPG levels occurred in men more than in women 47 .…”
Section: Discussionmentioning
confidence: 85%
“…Also, a study among Arab and South Asian Residents in Kuwait presented men with more incidence of metabolic abnormalities including hypertension, elevated FPG, and TG in both Arabs and South Asian groups. Abnormal low levels of HDL-C, was seen in Arab men more than Arab women, but it was higher among Asian women than men 46 . In the East of Asia, specifically China, more women had an abnormal WC, HDL-C, TC, and LDL-C compared to men, whereas hypertension, elevated TG and FPG levels occurred in men more than in women 47 .…”
Section: Discussionmentioning
confidence: 85%
“…In both BMI- and WC-defined obesity, our study found that the MuHO phenotype has the highest mean or median hs-CRP, ALT, and HOMA-IR values compared to other phenotypes. However, the relationship between these markers and MHO are of particular interest given the high prevalence of diabetes, obesity, and associated increased CVD risk in the Kuwait population [ 17 , 20 , 25 , 26 ], and the understanding that obesity is not invariably associated with adverse metabolic conditions [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1712 participants remained for analysis after the exclusion of records without hs-CRP measures. South Asian expatriates residing in Kuwait were predominantly from India, Pakistan, Sri Lanka, and Bangladesh; Arab groups were mainly from Kuwait, Egypt, Lebanon, Syria, Jordan, Iran, Palestine, and Yemen, as previously described [ 20 ]. Given that this is a secondary analysis of the data from the Kuwait Diabetes Epidemiology program, our prevalence estimates of MHO from this subsample (1712 participants) will be generalisable at 8% margin of error, and 90% confidence level, assuming a 24% baseline prevalence of MHO [ 21 ], and 40% non-response rate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations